Theoretical and numerical crush analysis of multi-stage nested aluminium alloy tubular structures under axial impact loading. (1st March 2019) - Tran, TrongNhan; Le, DucHieu; Baroutaji, Ahmad
Highlights: Nested multi-stage tubular thin-walled structures were subject to axial impact loads. Theoretical models for Average Crush Force of these structures are proposed. Numerical simulations were conducted to validated the theoretical models. The crashworthiness indictors were calculated and the best structure was determined. Abstract: In this paper, the crush behaviour and energy absorption performance of nested tubular thin-walled structures made of aluminium alloy AA6061-O under dynamic axial loading are investigated. Theoretical solutions for Average Crush Force ( P acf ) of these structures are proposed by combining the energy method, simple superposition principle, and interaction among the various components of the structures. The derived theoretical models are verified by comparing their predictions with numerical and experimental values. The energy absorption indicators of the various structures are calculated and used to compare the various structures and to determine the best performing one. It is found that the nested structure with a higher number of tubes exhibits the best crashworthiness performance due to energy absorption enhancements resulted from the interaction effects between its components as well as its capability to reduce the peak crush force.